Issues And Challenges In Social Work Profession: Perspectives Of Social Workers Of Assam - ROY, MONALISHA PHUKAN; BORBORA, PROF. SEEMA VERMA q (The journal of contemporary issues in business and government, 2021)
Social work being a helping profession has its root in ancient times of India. It was believed then to be a sanctified obligation which in return aided a person to gain a sense of fulfillment. However it can be seen during Ashokas reign, the helping process got institutionalized. Gradually, in 1843, Association of Improving Conditions of the Poor (AICP), USA recognized that mere charity cannot solve the problems rather it created a permanent liability on society. It can be depicted as the inception of social work profession. Social work as a profession is quite novice in comparison with other professions e.g., Medicine. Unlike other professions, social work encompasses a broad field of interventions: macro, mezzo and micro level. Due to the expansion of the profession in such colossal dimension, it becomes a herculean task to retain its professional identity in an unambiguous manner. Even after completing 85 years of glorious journey, social work has not gained impetus as a profession in India and is always subjected to debate and discussion. Assam lies in the easternmost part of India. Though very rich in her natural resources and cultural diversity, Assam is still lagging behind in terms of developmental perspectives. There is lack of industrialization, professional education etc. Apart from the mentioned crisis, other vital issues that is weeding up as a menace towards the safeguarding of serenity and harmony among North Eastern states is borderline conflicts. Assam having a landscape and potential racial, lingual and ethnic diversity which creates ethnic tensions and conflict. Infiltration is another burning issue that is devouring the state of Assam precisely. Social work has to deal with the by-products of the above mentioned problems. However, there is still a lack of awareness about social work profession among the public in general and administration of the state in particular which actually makes the social workers ambiguous about their identity. The purpose of this study is to understand the status of social work profession in Assam and also to assess the challenges and issues faced by the social workers in Assam. The paper is based on empirical findings. It will be highlighting the perspective of the social workers towards their future scope being a social work professional and issues faced by them in their professional lives in Assam. It was conducted by taking 60 social workers as respondents working in various sectors (government and non- government) of Assam.